Gut microbiota, chronic inflammation and metabolic syndrome - Gewirtz, Andrew (Henry Stewart Talks, 2012)
Managing intestinal bacteria, Toll-like receptors, Flagellin, Enhancing inflammation through blockade of a pro-inflammatory signaling pathway, T5KO mice, Embryo transfer, Loss of TLR5 and alteration of the composition of the gut microbiota, Possible role of gut microbiota in metabolic syndrome and relevance in humans, The human gut microbiota in the last 50-100 years, Dietary disturbance of the gut microbiota & metabolic syndrome
Updated at 2018/02/28